2018
DOI: 10.3390/nu10081110
|View full text |Cite
|
Sign up to set email alerts
|

Postprandial Glycaemic, Hormonal and Satiety Responses to Rice and Kiwifruit Preloads in Chinese Adults: A Randomised Controlled Crossover Trial

Abstract: Controlling postprandial glycaemia helps to prevent and manage non-communicable diseases. One strategy in controlling glycaemia may be to consume meals in two parts; a preload, followed by the remainder of the meal. Our aim was to test preloading a rice meal given for breakfast and lunch on different days, either by splitting the meal (rice preload followed by rice meal) or by using kiwifruit as a preload compared with consuming the rice meal in one sitting. Primary outcomes were glycaemic and insulinaemic res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 52 publications
1
20
0
Order By: Relevance
“…A previous study observed a significant reduction in insulin response and an increase in glucagon level after a kiwifruit preload [20]. In a study on gastrointestinal hormone responses, it was found that the ingestion of 30 g fructose had little impact on insulin, GIP, and GLP-1 [39].…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…A previous study observed a significant reduction in insulin response and an increase in glucagon level after a kiwifruit preload [20]. In a study on gastrointestinal hormone responses, it was found that the ingestion of 30 g fructose had little impact on insulin, GIP, and GLP-1 [39].…”
Section: Discussionmentioning
confidence: 90%
“…Since such a small dose of sugar made a difference to postprandial GR of a high GI diet, we inferred that the sugars in an apple are likely to act as an important factor in its GR effect. A previous study found that kiwifruit preload containing 25 g carbohydrate reduced the iAUC 0-120 by 29.8%, cut the peak glucose value by 1.1 mmol/L, compared with the water-preload control [20]. However, the researchers concluded that it was the non-sugar components that improved GR profile to co-ingested cereal food, for the co-ingestion of kiwifruit sugar failed to reduce the GR of a wheat biscuit meal as the kiwifruit did [41].…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Drinking tea together with carbohydrate is also an effective method to inhibit digestive enzymes (Nyambe-Silavwe & Williamson, 2016). Kiwifruit showed a small (0.9 mmol/L) reduction in glycemic peak when consumed as a preload to rice (Lubransky et al, 2018). Longterm consumption of fenugreek seed extract before meals over 2 months also showed reduced insulin resistance and improved glycemic control in diabetic subjects (Gupta, Gupta, & Lal, 2001).…”
Section: Polysaccharides (Dietary Fiber) and Polyphenolsmentioning
confidence: 99%